Joint communication: Developing a European Union Policy towards the Arctic Region: progress since 2008 and next steps. - European Union, EU
As climate change and economic development accelerate in the Arctic region, the European Union should step up its engagement with its Arctic partners to jointly meet the challenge of safeguarding the environment while ensuring the sustainable development of the Arctic region. Nowhere is climate change more visible than in the Arctic, which is a vital and vulnerable component of the Earth's environment and climate system. The melting of the Arctic sea ice is progressing rapidly, resulting in self-accelerating global warming, and affecting ecosystems as well as the traditional livelihoods of indigenous peoples.